EEG correlates of a mental arithmetic task in patients with first episode schizophrenia and schizoaffective disorder - Garakh, Zhanna; Zaytseva, Yuliya; Kapranova, Alexandra; Fiala, Ondřej; Horacek, Jiri; Shmukler, Alexander; Gurovich, Isaac Ya; Strelets, Valeria B (Clinical neurophysiology, 2015)
OBJECTIVE: To evaluate the spectral power of the cortical bands in patients with first episode schizophrenia and schizoaffective disorder at rest and during the performance of a mental arithmetic task. METHODS: We analyzed EEG spectral power (SP) in the resting state and subsequently while counting down from 200 in steps of 7, in 32 first episode schizophrenia patients (SZ), 32 patients with first episode schizoaffective disorder (SA) and healthy controls (HC, n=40). Behavioral parameters such as accuracy and counting speed were also evaluated. RESULTS: Both SZ and SA patients were slower in counting than HC, no difference was obtained in the accuracy and counting speed in the patient groups. In the resting state patients showed elevated midline theta power, off-midline anterior beta 2 power and decreased central/posterior alpha power. The SA group occupied an intermediate position between the schizophrenia patients and controls. In task performance patients lacked a typical increase of midline theta, left anterior beta 2, and anterior gamma power; however, schizoaffective patients demonstrated a growing trend of power in the gamma band in left anterior off-midline sites similar to HC. Moreover, alpha power was less inhibited in schizoaffective patients and more pronounced in schizophrenia patients indicating distinct inhibitory mechanisms in these psychotic disorders. CONCLUSIONS: Patients with SA demonstrate less alteration in the spectral power of bands at rest than SZ, and present spectral power changes during cognitive task performance close to the controls. SIGNIFICANCE: Our study contributes to the present evidence on the neurophysiological distinction between schizophrenia and schizoaffective disorder.
Keywords: Adolescent; matematika; Task Performance and Analysis; Male; Female; Theta Rhythm; mladý dospělý; Middle Aged; Young Adult; beta rytmus EEG; Rest; Electroencephalography; plnění a analýza úkolů; Psychotic Disorders; Schizophrenia; mapování mozku; odpočinek; mužské pohlaví; kognice; elektroencefalografie; ženské pohlaví; Adult; Alpha Rhythm; mladiství; Beta Rhythm; schizofrenie; dospělí; Mathematics; lidé středního věku; alfa rytmus EEG; studie případů a kontrol; Cognition; psychotické poruchy; lidé; Brain Mapping; Humans; theta rytmus EEG; Case-Control Studies